Results obtained with a low cost software-based audiometer for hearing screening - Ferrari, Deborah Viviane; Lopez, Esteban Alejandro; Lopes, Andrea Cintra; Aiello, Camila Piccini; Jokura, Pricila Reis (International Archives of Otorhinolaryngology, 2013)
Introduction: The implementation of hearing screening programs can be facilitated by reducing operating costs, including the cost of equipment. The Telessaúde (TS) audiometer is a low-cost, software-based, and easy-to-use piece of equipment for conducting audiometric screening.Aim: To evaluate the TS audiometer for conducting audiometric screening.Methods: A prospective randomized study was performed. Sixty subjects, divided into those who did not have (group A, n = 30) and those who had otologic complaints (group B, n = 30), underwent audiometric screening with conventional and TS audiometers in a randomized order. Pure tones at 25 dB HL were presented at frequencies of 500, 1000, 2000, and 4000 Hz. A “fail” result was considered when the individual failed to respond to at least one of the stimuli. Pure-tone audiometry was also performed on all participants. The concordance of the results of screening with both audiometers was evaluated. The sensitivity, specificity, and positive and negative predictive values of screening with the TS audiometer were calculated.Results: For group A, 100% of the ears tested passed the screening. For group B, “pass” results were obtained in 34.2% (TS) and 38.3% (conventional) of the ears tested. The agreement between procedures (TS vs. conventional) ranged from 93% to 98%. For group B, screening with the TS audiometer showed 95.5% sensitivity, 90.4% sensitivity, and positive and negative predictive values equal to 94.9% and 91.5%, respectively.Conclusions: The results of the TS audiometer were similar to those obtained with the conventional audiometer, indicating that the TS audiometer can be used for audiometric screening.
Keywords: Hearing; Hearing Loss; Hearing Tests